The eagle huntress [videorecording (DVD)] - Ridley, Daisy, 1992- (Sony Pictures Home Entertainment, 2017)
Follows Aisholpan, a 13-year-old girl, as she trains to become the first female in twelve generations of her Kazakh family to become an eagle hunter, and rises to the pinnacle of a tradition that has been typically been handed down from father to son for centuries.